Analisis Perencanaan dan Pengadaan Obat di Instalasi Farmasi RSUD Sultan Fatah Kabupaten Demak - Mulyati, Muji; Setyawan, Henry; Martini, Martini (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Pharmaceutical services are a critical aspect of patient care with a focus on pharmaceutical preparations to achieve definite results and improve the patient's quality of life. Management of pharmaceutical supplies is very important because inefficiency will have a negative impact on hospitals, both medically and economically. This research aims to analyze the planning and procurement of medicines at the Pharmacy Installation at Sultan Fatah Regional Hospital, Demak, using a qualitative approach through in-depth interviews, observation and document review, processing the data in this research using a content analysis approach. The research subjects consisted of 4 main informants and 3 triangulation informants. Drug management in the planning and procurement process has been implemented according to standards, but is not yet optimal. There are still obstacles, namely the condition stage due to new collaboration with BPJS, the presence of Covid-19 and the lack of drug classification at SIMRS at Sultan Fatah Regional Hospital. Keywords: Pharmaceutical Management, Planning, Procurement, Hospital  ABSTRAK Pelayanan Farmasi merupakan aspek kritis dalam perawatan pasien dengan fokus pada sediaan farmasi untuk mencapai hasil yang pasti dan meningkatkan mutu kehidupan pasien.  Pengelolaan perbekalan farmasi sangat penting karena ketidakefisienan akan memberikan dampak negatif terhadap rumah sakit, baik secara medis maupun ekonomis. Penelitian ini bertujuan untuk menganalisis perencanaan dan pengadaan obat di Instalasi Farmasi RSUD Sultan Fatah Demak dengan menggunakan pendekatan kualitatif melalui wawancara mendalam, observasi serta telaah dokumen, pengolahan data dalam penelitian ini menggunakan pendekatan analisa isi (content analysis). Subjek penelitian terdiri dari 4 orang informan utama dan 3 orang informan triangulasi. Pengelolaan obat pada proses pecencanaan dan pengadaan sudah dilaksanakan sesuai dengan standar, namun belum optimal. Masih terdapat kendala yaitu tahap adaptasi karena baru bekerjasama dengan BPJS, adanya covid-19 serta belum adanya penggolongan obat pada SIMRS di RSUD Sultan Fatah. Kata Kunci: Manajemen Farmasi, Perencanaan, Pengadaan, Rumah Sakit